On weak convergence of solutions of random perturbed evolution equations - Kolomiets, Yu. V. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We consider the weak convergence of measures generated by solutions of linear evolution equations depending on diffusion processes to the Gaussian measure as a small parameter tends to zero.